The Egocentric Nature of Action-Sound Associations - Navolio, Nicole; Lemaitre, Guillaume; Forget, Alain; Heller, Laurie M. (Frontiers in Psychology, 2016)
Actions that produce sounds infuse our daily lives. Some of these sounds are a natural consequence of physical interactions (such as a clang resulting from dropping a pan), but others are artificially designed (such as a beep resulting from a keypress). Although the relationship between actions and sounds has previously been examined, the frame of reference of these associations is still unknown, despite it being a fundamental property of a psychological representation. For example, when an association is created between a keypress and a tone, it is unclear whether the frame of reference is egocentric (gesture-sound association) or exocentric (key-sound association). This question is especially important for artificially created associations, which occur in technology that pairs sounds with actions, such as gestural interfaces, virtual or augmented reality, and simple buttons that produce tones. The frame of reference could directly influence the learnability, the ease of use, the extent of immersion, and many other factors of the interaction. To explore whether action-sound associations are egocentric or exocentric, an experiment was implemented using a computer keyboard’s number pad wherein moving a finger from one key to another produced a sound, thus creating an action-sound association. Half of the participants received egocentric instructions to move their finger with a particular gesture. The other half of the participants received exocentric instructions to move their finger to a particular number on the keypad. All participants were performing the same actions, and only the framing of the action varied between conditions by altering task instructions. Participants in the egocentric condition learned the gesture-sound association, as revealed by a priming paradigm. However, the exocentric condition showed no priming effects. This finding suggests that action-sound associations are egocentric in nature. A second part of the same session further confirmed the egocentric nature of these associations by showing no change in the priming effect after moving to a different starting location. Our findings are consistent with an egocentric representation of action-sound associations, which could have implications for applications that utilize these associations.